Peningkatan Kemampuan Membaca Cerita Anak Menggunakan Model CIRC Siswa Kelas V SD - Oktavia, Refma; sukma, Elfia; Zaiyasni, Zaiyasni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research is to describe the improvement of comprehension reading skill by using Cooperative Integrated Reading and Composition (CIRC) model for fifth grade students of SDN 08 Kota Padang. Research subjects were teachers as observers, researchers, and fourth graders as many as 26 people consisting of 12 men and 14 women. In the first cycle, I obtained an average value of preread 48.6, an average value of reading 56.3, and an average value of post-reading 64.5. In cycle II the average value of preread 80.3, the average value of reading 89.9, and the average value of 85.3 post-reading. Thus reading comprehension with model CIRC can improve in class V SDN 08 Kota Padang.Keywords: reading comprehension, cooperative integrated reading and composition.